Utilização de farinha de quinoa no desenvolvimento de pães sem glúten - Nobre, Ana Rita Melo Oliveira [UNESP] (2015)
Celiac disease is characterized by permanent intolerance to gluten and its only definitive treatment is the exclusion of this protein complex of the diet. However, adherence to this type of diet has a great impact on celiac's lives, since the availability of gluten-free products is restricted and limited sensory. The formulation of gluten-free products, especially bread, is a technological challenge, due to the important role of this protein in the physical structure of the baked goods. Quinoa (Chenopodium quinoa Willd) is a pseudo-cereal with outstanding nutritional value. Thus, this study aimed to develop gluten-free breads with different levels of quinoa flour, to evaluate physical-chemical and sensory characteristics and to determine the possible uses of this pseudo-cereal in preparing gluten-free breads. The breads were formulated from mixtures of rice flour, potato starch and quinoa flour, modeled through a simplex-centroid design. Analysis of volume, crumb firmness and color were performed and allowed the selection of formulations with quinoa flour content between 17% and 33% that showed suitable physical characteristics. Sensory analyzes of these formulations, of the standard formulation of gluten-free bread made without the addition of pseudo-cereal and of a commercial gluten-free bread were conducted in order to compare the acceptability of these different products. The inclusion of 33% of quinoa in the mixture decreased bread's flavour and overall acceptability in comparison to the standard bread. The bread containing 17% of quinoa flour was similar to the standard product and it was preferred by tasters. Analysis of the chemical composition of this formulation has shown a 44% increase in total dietary fiber content compared to the conventional product. Significant increase in the mineral content was also observed. It can be seen, therefore, the viability of production of gluten-free...